As faces da produção do espaço urbano na cidade de São Paulo e no Conjunto Habitacional José Bonifácio - Pires, Flavia Cristina de Paula Gomes (2012)
The object of this dissertation was the production of urban space by a public service provider, with emphasis on implementation by COHAB/SP, of housing developments during the period 1960 to 1980. The case of José Bonifácio Housing was used as the empirical field. The investigation focused on the elements that, by the involvement or non-involvement of the State, contributed to the design of urban space production in São Paulo; and how the housing built by the Metropolitan Housing Company of São Paulo (COHAB/SP) influenced this production. The methodology included both the literature and field research, through interviews. To understand the object of analysis several factors were considered: the theoretical framework on the production of space, the national and municipal housing policies, and the housing provision through COHAB/SP. The research showed that the production of urban space in José Bonifácio Housing, sponsored by the State, had the same low quality in providing services and urban infrastructure equipment as that of clandestine/irregular allotments. The research also verified that the three types of finished public housing the apartment or house, the house built in a system of mutual help and the self-constructed home in an "invaded" area were responsible for the configuration of the landscape and the transfer of stigma among the residents. As a challenge, the study points out the need for a new configuration of urban space; the equating of the illegal and legal mechanisms for the provision of housing; the heterogeneity of the territories of the city; the need of analyzes that address the specifics in the settlements; and the new production parameters of urban space